2016
DOI: 10.2140/agt.2016.16.1727
|View full text |Cite
|
Sign up to set email alerts
|

L-space surgery and twisting operation

Abstract: A knot in the 3-sphere is called an L-space knot if it admits a nontrivial Dehn surgery yielding an L-space, i.e. a rational homology 3-sphere with the smallest possible Heegaard Floer homology. Given a knot K, take an unknotted circle c and twist K n times along c to obtain a twist family { K_n }. We give a sufficient condition for { K_n } to contain infinitely many L-space knots. As an application we show that for each torus knot and each hyperbolic Berge knot K, we can take c so that the twist family { K_n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…While no example in [45] appears to give a positive answer to this question, we still expect such a twist family to exist.…”
Section: Questionsmentioning
confidence: 93%
See 2 more Smart Citations
“…While no example in [45] appears to give a positive answer to this question, we still expect such a twist family to exist.…”
Section: Questionsmentioning
confidence: 93%
“…In this section we investigate Conjectures 1.2 and 1.3 from a viewpoint of braids. We have observed that for many of the twist families containing infinitely many L-space knots that are studied in [45], the twisting circle is not only a seiferter but also a braid axis. Furthermore, L-space knots are often isotopic to closures of positive or negative braids.…”
Section: Braids and L-space Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain an explicit picture of the covering knot K of κ, we apply isotopies given in Figs. [10][11][12][13][14][15]. Then taking the…”
Section: A Hyperbolic L-space Knot With No Exceptional Surgeriesmentioning
confidence: 99%
“…Note that P (−2, 3, 2n + 1) with n ≥ 0 admits a Seifert fibered L-space surgery [10,16]. One can find a large number of twist families of hyperbolic L-space knots each of which admits a Seifert fibered L-space surgery; see [14]. To the best of our knowledge, there are no explicitly known examples of hyperbolic L-space knots which have no Seifert fibered L-space surgeries, though we expect there should be many.…”
Section: Introductionmentioning
confidence: 99%